El espacio rural en una sociedad urbana: valoración ambiental y paisajística. - Moreno Sanz, Fernando; Navalpotro, Paulino; Sancho Comíns, José; Santaolalla, Antonio (Anales de Geografía de la Universidad Complutense, 1995)
Sin resumen